Interface Coassembly and Polymerization on Magnetic Colloids: Toward Core–Shell Functional Mesoporous Polymer Microspheres and Their Carbon Derivatives. Issue 12 (30th April 2020) - Pan, Panpan; Zhang, Tong; Yue, Qin; Elzatahry, Ahmed A.; Alghamdi, Abdulaziz; Cheng, Xiaowei; Deng, Yonghui
Abstract: Core–shell structured magnetic mesoporous polymer or carbon‐based microspheres not only possess the combined merits of magnetic particles and stable mesoporous shell but also provide various organic functional groups for further modification and immobilization of active sites, thus opening up more possibility for various applications. Herein, a bottom‐up soft‐templating strategy is developed to controllably synthesize core–shell magnetic mesoporous polydopamine microspheres (MMP) and their derivative magnetic mesoporous carbon (MMC) microspheres via an amphiphilic block copolymer‐directed interface assembly and polymerization (denoted as abc‐DIAP) approach. The obtained uniform MMP microspheres have a well‐defined structure consisting of magnetic core, silica middle layer and mesoporous PDA shell, uniform mesopores of 11.9 nm, high specific surface areas (235.6 m 2 g −1 ) and rich functional groups. They show fast magnetic separation speed and superior performance in selective adsorption of Cyt.C from complex biosample solutions. Moreover, they can be in situ converted into core–shell magnetic mesoporous carbon (MMC) for efficient in‐pore immobilization of ultrafine Au nanoparticles for high‐efficiency catalytic epoxidation of styrene with high conversion (88.6%) and selectivity (90.1%) toward styrene oxide. Abstract : An interfacial coassembly and polymerization is developed for the fabrication of core–shell magnetic mesoporous polymers with ordered and accessible mesopore. The obtained well‐defined and tailorable core–shell magnetic polymers possessing abundant functional organic groups show potential applications in enzyme immobilization and size‐selective enrichment. The derived magnetic mesoporous carbon microspheres exhibit desirable carriers for loading noble metal nanoparticles and heterogeneous catalysis.